Variações morfológicas e texturais de quartzo do Granito Antônio Vicente, Província Estanífera do Sul do Pará, reveladas através de imagens de MEV-catodoluminescência - ROCHA, Kellen Katucha Nogueira (Universidade Federal do Pará, 2019)
The Antonio Vicente Granite (AVG), located in the northwest of Sao Felix do Xingu, Carajás Province, is one of the bodies of the Velho Guilherme Intrusive Suite. It consists of isotropic syenogranite to monzogranite hololeucocratic to leucocratic rocks altered in different intensities by late to post-magmatic processes. The AVG hosts mineralization of Sn and other metals (Ta, Nb, Zr, Y) in its more evolved rocks and associated bodies of greisens. Geochemically, presents metaluminous to weakly peraluminous character, signature of A-type granites, and geotectonic affinity with intraplate granites. Four major petrographic domains were recognized: (1) Biotite-amphibole monzogranite to syenogranite (BASMG), preserved of late to post-magmatic alterations, (2) Amphibole-biotite syenogranite (ABSG), (3) Biotite monzogranite (BMG) and , (4) Biotite syenogranite (BSG) with variations to types altered and intensely altered, called, respectively, Altered biotite syenogranite (ABSG) and Intensely altered biotite syenogranite (IABSG). Tabular bodies of greisens occur in fractures and faults into syenogranite rocks. Petrographic and geochemical studies show that fractional crystallization was the major petrogenetic process that governed the evolution of this body. Five types of quartz were identified based on morphological and textural analysis using SEM CL: Qz1, luminescent, anhedral, fractured, medium to-coarse grained, locally zoned, present in all facies and considered the earlier type. Qz2, little luminescent, it forms irregular patches or discontinuous gray to dark gray edges on the Qz1; it is present in greater intensity in the more evolved rocks. Qz3, considered the later type, show black color and fills microfractures, sectioning previous types. It is rarer in greisens associated with AVG. Qz4, identified in the IABSG rocks and greisens, it forms well developed anhedral crystals, slightly fractured and with variable luminescence. It seems to mark the transition from magmatic to hydrothermal stage. Qz5, it was identified only in bodies of greisens or filling cavities in IABSG. It appears as euhedral crystals slightly fractured, sometimes forming clusters of fine crystals. It shows light-dark zoning in a typically well-defined hydrothermal pattern. Crystals of cassiterite are commonly associated with Qz4 and Qz5 types. The morphological and textural features suggest that magmatic quartz (Qz1) was modified and transformed into Qz2 and Qz3 by hydrothermal fluids that percolated the AVG. These alterations are more intense in the ABSG and IABSG. In the greisens, quartz crystals show typically hydrothermal quartz pattern. Preliminary chemical analysis by LA-ICP-MS on quartz crystals showed significant changes mainly in the contents of Ti, Al and Ge. The continuous decrease in the content of Ti with the differentiation of the AVG confirmed the compatible behavior of this element in granitic rocks and showed a negative correlation with Rb/Sr whole rock. Al showed a more irregular behavior, but decreased in the same direction. The Ge, considered a good indicator of magmatic differentiation, presented constant Ge/Ti ratios in the syenogranite and monzogranite rocks, but higher in intensely altered rocks and in the greisen, been a good indicator of magmatic evolution in granitic systems. The study of SEM-CL showed that quartz was an excellent marker of the changes imposed by the late to post-magmatic process that acted in the AVG. This study opens a new line of research in the GI of the UFPA, making this an important tool in geological studies.